Social and cognitive development in the context of individual, social, and cultural processes - Raeff, Catherine, 1964-; Benson, Janette B., 1956- (Routledge international library of psychology, 2003)
This volume showcases varied theoretical and empirical approaches to how individual, social and cultural factors shape development, and suggests new directions for future scholarship.